Economic and legal challenges of virtual money: the central banks issuance - Barossi-Filho, Milton; Sztajn, Rachel; Rossi Mazzoni, João Fernando (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2023)
Money is an ancient and convenient commodity. Throughout history, however, convenience and security posed a dilemma that was overcome only two centuries ago. Notwithstanding fiat currency being a consolidated matter, its wide acceptance as a secure means for exchanges started collapsing in the last fifty years after Bretton Woods’ crises. In this sense, a substantial number of resources has been allocated to studying the possibilities for introducing digital money, especially by central banks. Concurrently on this concern, other digital money has been circulating in the entire economic system without any legal tender, legitimating the relevancy of the discussion on legal aspects of this sort of commodity classified promptly as res. Circulating without any monetary authority, adequate supervision, and lacking convertibility guarantee in any other currency and legal tender as well, the market for cryptocurrencies can lead to financial disasters once typical legal tender money liquidity is missing. Although these issues are a matter of concern, digital currency creation is not illegal, but economic impediments arise to define them as complete means of payment. Opposing economic and legal arguments, the possibility of digital money creation by central banks is a point for discussion because it possibly will substitute fiat money. Based on these arguments, this paper opens some room for thinking about a possible legal discipline for central banks’ digital money issues, which means assigning legal tender to them.